Galactan synthesis in a single step via oligomerization of monosaccharides - Dräger, Marius; Basu, Amit (Beilstein Journal of Organic Chemistry, 2014)
Galactans ranging in length from one to five residues were prepared in a single step by treatment of the glycosyl donor 2,3,4-tri-O-benzoyl-β-D-galactopyranosyl fluoride with lanthanum perchlorate in the presence of an initiator alcohol. The product oligosaccharides were readily chromatographically separable. This oligomerization was used to synthesize a pentagalactan in a single step from monosaccharide building blocks in reasonable overall yields.
Keywords: arabinogalactan protein; glycosyl fluoride; glycosylation; oligosaccharides